(untitled) (Research, Society and Development, 2022)
The increased incidence of childhood obesity is one of the most worrying topics today, as this is a condition that favors the onset of chronic diseases in adulthood, such as diabetes and hypertension. In the recent scenario of the pandemic of the new coronavirus, social isolation in conjunction with the closure of schools contributed significantly to the increase in the prevalence of overweight children, as there was a reduction in the routine practice of physical exercises and favored the consumption of hypercaloric foods with low nutritional quality. The study aimed to determine the rate of childhood overweight and obesity of patients seen from July to December 2020 in three Basic Health Units (BHU) in Cascavel/PR through a descriptive comparative method, using references from consultations before and after the pandemic. Body mass index (BMI) data from medical records of 213 children were evaluated. Of the total number of patients, 114 (53.5%) experienced weight gain during the pandemic. A significant portion of patients had an unbalanced diet and anxiety disorder was the associated comorbidity most reported by family members in the medical records. Several aspects of the research are in line with what was expected about the consequences of the pandemic, and the weight gain could be verified. It was concluded that there was an increase in the prevalence of overweight and/or obesity as a consequence of the changes imposed by the pandemic, more studies should be carried out to analyze the degree of future impairment of these children, also highlighting the assessment of mental health in this population.